Associations between Serum Omega-3 Fatty Acid Levels and Cognitive Functions among Community-Dwelling Octogenarians in Okinawa, Japan: The KOCOA Study - Nishihira, Junko; Tokashiki, Takashi; Higashiuesato, Yasushi; Willcox, Donald Craig; Mattek, Nora; Shinto, Lynne; Ohya, Yusuke; Dodge, Hiroko H (Journal of Alzheimer's disease, 2016)
Epidemiological studies have found frequent consumption of fatty fish is protective against cognitive decline. However, the association between circulating omega-3 polyunsaturated fatty acid (PUFA) levels and cognitive functions among the oldest old is not well known. To examine the association between serum PUFA levels and cognitive function among community-dwelling, non-demented elderly aged over 80 years old. The data came from the Keys to Optimal Cognitive Aging (KOCOA) study; an ongoing cohort of relatively healthy volunteers aged over 80 years old, living in Okinawa, Japan. One hundred eighty five participants (mean age 84.1±3.4 years) assessed in 2011 who were free from frank dementia (defined as Clinical Dementia Rating <1.0) were used for the current cross-sectional study. We examined whether serum omega-3 PUFAs (docosahexaenoic acid [DHA] and eicosapentaenoic acid [EPA]), arachidonic acid (AA), EPA/AA ratio, DHA/AA ratio, and DHA+EPA are associated with (1) age and (2) global cognitive function (Japanese MMSE) and executive function (Verbal Fluency Letter). Data was analyzed univariately by t-test and multivariately by cumulative logistic regression models controlling for age, gender, years of education, obesity, hypertension, diabetes, and dyslipidemia. Serum DHA levels decreased with increasing age (p = 0.04). Higher global cognitive function was associated with higher levels of serum EPA (p = 0.03) and DHA + EPA (p = 0.03) after controlling for confounders. Higher serum EPA and DHA + EPA levels were independently associated with better scores on global cognitive function among the oldest old, free from dementia. Longitudinal follow-up studies are warranted.